Factors affecting use of information communication technologies among extension agents in North-East, Nigeria - Sa’adu, Mustapha; Man, Norsida; Arif Shah, Jasmin; Kamarulzaman, Nitty Hirawaty; Tafida, Ahmadu Abubakar (Agricultural Extension Society of Nigeria, 2022)
The study identified the levels of ICT use, awareness, accessibility, perceived organizational support, assessed the perception of the respondents on problems in using ICTs for agriculture extension work and, clarifies the relationships between awareness, accessibility, perceived organizational support, and use of ICTs. Data were collected through the use of a questionnaire distributed to 254 respondents using a multi-stage sampling and stratified sampling procedures. Mean, frequency, standard deviation and structural equation modelling in analysis of morement structure (AMOS) was used. Findings revealed that levels of ICT use (x̄ = 3.43), awareness (x̄ =3.40) accessibility (x̄ 3.66), and perceived organizational support (x̄ 3.574) were moderates. The high cost of ICT garget (x̄ =4.71), poor electricity supply (x̄ =4.69), lack of training (x̄ =4.63), ICT illiteracy (x̄ =4.61), outdated contents (x̄ =4.61), inability to use ICT (x̄ =4.55) and network issue (x̄ =4.34) were the critical problems in using ICTs in extension work. There was relationship between awareness, accessibility and motivation with ICT adoption among extension agents. Governments should design a policy that will focus on awareness, training, access to ICTs among the extension agents, provide an alternative source of power, this will enable them to remain within the system and also increase their usage of ICTs in extension service delivery.